Disease burden and health-care clinic attendances for young children in remote aboriginal communities of northern Australia - Danielle B Clucas; Kylie S Carville; Christine Connors; Bart J Currie; Jonathan R Carapetis; Ross M Andrews (The World Health Organization, 2008)
OBJECTIVE: To determine the frequency of presentations and infectious-disease burden at primary health care (PHC) services in young children in two remote Aboriginal communities in tropical northern Australia. METHODS: Children born after 1 January 2001, who were resident at 30 September 2005 and for whom consent was obtained, were studied. Clinic records were reviewed for all presentations between 1 January 2002 and 30 September 2005. Data collected included reason for presentation (if infectious), antibiotic prescription and referral to hospital. FINDINGS: There were 7273 clinic presentations for 174 children aged 0-4.75 years, 55% of whom were male. The median presentation rate per child per year was 16 (23 in the first year of life). Upper-respiratory-tract infections (32%) and skin infections (18%) were the most common infectious reasons for presentation. First presentations for scabies and skin sores peaked at the age of 2 months. By 1 year of age, 63% and 69% of children had presented with scabies and skin sores, respectively. CONCLUSION: These Aboriginal children average about two visits per month to PHC centres during their first year of life. This high rate is testament to the disease burden, the willingness of Aboriginal people to use health services and the high workload experienced by these health services. Scabies and skin sores remain significant health problems, with this study describing a previously undocumented burden of these conditions commencing within the first few months of life. Appropriate prevention and treatment strategies should encompass early infancy to reduce the high burden of infectious diseases in this population.